The rise of artificial intelligence: a concise review - Rama Padmaja, Chinimilli Venkata; Lakshmi Narayana, Sadasivuni; Latha Anga, Gouthami; Kumari Bhansali, Priyanka (Institute of Advanced Engineering and Science, 2024)
Artificial intelligence (AI) has emerged as a transformative force with farreaching implications across various domains. This research review provides a concise analysis of the rise of AI, examining its evolution, applications, ethical considerations, and future prospects. The study traces the historical development of AI, highlighting key milestones and technological advancements that have propelled its growth. It explores the wide-ranging applications of AI in sectors such as healthcare, finance, transportation, manufacturing, human resource management and entertainment, showcasing its impact on efficiency, decisionmaking, and user experiences. Ethical considerations surrounding AI, including bias, privacy, and societal implications, are thoroughly discussed. The transformative potential of AI in shaping society is expolred, with insights into its effects on employment, education, governance, and societal challenges. Looking ahead, the review identifies emerging technologies and discusses challenges related to data privacy, security, and transparency. The research review concludes by emphasizing the importance of responsible and ethical development of AI, while underscoring the need for continued research and collaboration to fully harness its potential. This review serves as a valuable resource for researchers, and practitioners seeking a holistic understanding of the rise of AI and its implications.